1999
DOI: 10.1002/(sici)1097-4547(19990401)56:1<76::aid-jnr10>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the extracellular profiles of neuroactive amino acids in the rat striatum at the asymptomatic stage of hepatic failure

Abstract: Rats were treated with a hepatotoxin thioacetamide (TAA) and examined 21 days later, when they showed moderate fatty metamorphosis of the liver and morphological changes in brain indicative of excitotoxic neuronal damage, but no evident biochemical or neurophysiological symptoms of hepatic encephalopathy (HE). High-performance liquid chromatography (HPLC) analysis of extracellular amino acids in striatal microdialysates of TAA-treated rats revealed a significant increase in the excitatory amino acids glutamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…An increase in extracellular brain glutamate has been consistently demonstrated in different animal models of ALF, 24,[35][36][37][38] which could be the result of decreased glutamate uptake or increased glutamate release. 39 It has been recently demonstrated that an acute insult of ammonia leads to glutamate release from astrocytes.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in extracellular brain glutamate has been consistently demonstrated in different animal models of ALF, 24,[35][36][37][38] which could be the result of decreased glutamate uptake or increased glutamate release. 39 It has been recently demonstrated that an acute insult of ammonia leads to glutamate release from astrocytes.…”
Section: Discussionmentioning
confidence: 93%
“…In patients suffering from acute liver failure, glutamatergic dysfunction (Hilgier et al, 1999;Michalak et al, 1996) resulted from high levels of brain ammonia (1-3·mmol·l…”
mentioning
confidence: 99%
“…A consistent finding in experimental animal models of ALF is that of increased extracellular brain glutamate (Bosman et al, 1992;de Knegt et al, 1994;Hilgier et al, 1999;Michalak et al, 1996). This increased extracellular brain glutamate leads to increased glutamatergic neurotransmission which has been suggested to be implicated in the pathogenesis of CNS complications of ALF (Butterworth, 1997).…”
Section: The Pathophysiology Of Hypothermia-effect On the Brainmentioning
confidence: 83%
“…Clinically, extracellular brain lactate concentrations were found to increase in association with increased ICP in patients with ALF (Tofteng et al, 2002). It has also been demonstrated that alanine is elevated in the hyperammonemic brain (Hilgier et al, 1999;Mans et al, 1994;Swain et al, 1992) and more recently in rats with ALF using nuclear magnetic resonance (NMR) spectroscopy (Chatauret et al, 2003). Increased lactate and alanine production indirectly suggest that anaerobic pathways (increased glycolytic activity) may be stimulated to compensate for a decreased pyruvate oxidation (due to ammonia inhibition on the enzyme alpha-ketoglutarate dehydrogenase in the tricarboxylic acid cycle (Lai and Cooper, 1986)) and maintain ATP production.…”
Section: The Pathophysiology Of Hypothermia-effect On the Brainmentioning
confidence: 95%